Art for Foulkes' Sake or How I Learned to Stop Worrying and Trust the Group. (March 2016) - Power, Kevin
This article addresses the title of the GASI's 15th Symposium in Lisbon, 'Group-Analysis as Art and Science'. It is eclectic and seeks to expose some fallacies in certain areas of practice and theory, and questions the trend towards medico-technological practice rather than valuing group analysis as a creative practice that contains much more for its participants than mere 'recovery'. The underlying argument is that the process-art of the group that the members participate in is the dynamo of change in the group.